2004
DOI: 10.1107/s0907444903025770
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and preliminary crystallographic analysis of rat monoamine oxidase A complexed with clorgyline

Abstract: Monoamine oxidase (MAO) is an FAD-containing mitochondrial outer-membrane protein which catalyzes the degradation of several neurotransmitters in the central nervous system. The two subtypes of MAO, MAOA and MAOB, have similar primary sequences but different substrate and inhibitor specificities. The structure of human MAOB has recently been determined, but the structure of MAOA remains unknown. To clarify the mechanisms underlying their unique substrate and inhibitor recognition and thereby facilitate the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…The application of recent technological developments in polynucleotide technology and the availability of the crystal structure for MAO-B [173], with the promise that the structure for MAO-A should soon be available from at least one source [174], have allowed some major advances, but there remain several grey areas about the regulation and functions of the enzymes. There will be a lot of fun, and probably some startling new discoveries, in the MAO field for many years to come.…”
Section: Resultsmentioning
confidence: 99%
“…The application of recent technological developments in polynucleotide technology and the availability of the crystal structure for MAO-B [173], with the promise that the structure for MAO-A should soon be available from at least one source [174], have allowed some major advances, but there remain several grey areas about the regulation and functions of the enzymes. There will be a lot of fun, and probably some startling new discoveries, in the MAO field for many years to come.…”
Section: Resultsmentioning
confidence: 99%
“…This behavior is consistent with available structural data showing the monopartite active site cavities of the two enzymes being quite similar. 8,26 …”
Section: Discussionmentioning
confidence: 99%
“…Although MAO‐A and its isoform MAO‐B have 70% amino acid identity, MAO‐A has a 500‐fold lower IC 50 for clorgyline than MAO‐B (Geha et al, 2001). In addition, both site‐directed mutagenesis and comparison of the crystal structures of MAO‐A and MAO‐B complexed with their inhibitors showed that a single amino acid in these two isoforms determines their substrate and inhibitor specificities (Geha et al, 2001; Ma et al, 2004). However, clorgyline also has other activities unrelated to inhibition of MAO‐A.…”
Section: Discussionmentioning
confidence: 99%